Autosomal dominant polycystic kidney disease and pioglitazone for its therapy: a comprehensive review with an emphasis on the molecular pathogenesis and pharmacological aspects - Aryendu Kumar Saini; Rakesh Saini; Shubham Singh (BMC, 2020)
Abstract Autosomal dominant polycystic kidney disease (ADPKD) is an inherited chronic kidney disorder (CKD) that is characterized by the development of numerous fluid-filled cysts in kidneys. It is caused either due to the mutations in the PKD1 or PKD2 gene that encodes polycystin-1 and polycystin-2, respectively. This condition progresses into end-stage renal disorder if the renal or extra-renal clinical manifestations remain untreated. Several clinical trials with a variety of drugs have failed, and the only Food and Drugs Administration (FDA) approved drug to treat ADPKD to date is tolvaptan that works by antagonizing the vasopressin-2 receptor (V2R). The pathology of ADPKD is complex and involves the malfunction of different signaling pathways like cAMP, Hedgehog, and MAPK/ERK pathway owing to the mutated product that is polycystin-1 or 2. A measured yet substantial number of preclinical studies have found pioglitazone to decrease the cystic burden and improve the renal function in ADPKD. The peroxisome proliferator-activated receptor-gamma is found on the epithelial cells of renal collecting tubule and when it gets agonized by pioglitazone, confers efficacy in ADPKD treatment through multiple mechanisms. There is only one clinical trial (ongoing) wherein it is being assessed for its benefits and risk in patients with ADPKD, and is expected to get approval from the regulatory body owing to its promising therapeutic effects. This article would encompass the updated information on the epidemiology, pathophysiology of ADPKD, different mechanisms of action of pioglitazone in the treatment of ADPKD with preclinical and clinical shreds of evidence, and related safety updates.